The Influence of Organizational Culture and Motivation on Employee Performance at Hotel Puri Dajuma Beach Eco Resort and Spa Jembrana - Rusmiati, Nyoman; Nugraha, Surya; Pusparini, Helena I Gusti Ayu Putu (Jurnal Manajemen Pelayanan Hotel, 2023)
The research in this thesis is motivated by how the influence of organizational culture and motivation on employee performance at Puri Dajuma Beach Eco Resort and Spa Jembrana Hotel. The purpose of this thesis research is to determine the effect of organizational culture and motivation on employee performance at Puri Dajuma Beach Eco Resort and Spa Jembrana Hotel. In this study, primary and secondary data are quantitative. The technique of testing the data in this study is the instrument test consisting of validity and reliability tests, while the classical assumption test consists of normality, multicollinearity, and heteroscedasticity tests and multiple linear regression tests where the significance level is 5 percent. The results showed that culture (X1) had a positive and significant effect on employee performance. From these results it can be seen that organizational culture is very important in the company. Motivation (X2) has a positive and significant effect on employee performance. The results of this study indicate that motivation has an important influence on the continuity of quality employee performance. Keywords: Organizational Culture, Motivation, and Employee Performance